The combined and individual impact of diabetes and smoking on key subgingival periodontal pathogens in patients with chronic periodontitis. (6th November 2017) - Joaquim, C. R.; Miranda, T. S.; Marins, L. M.; Silva, H. D. P.; Feres, M.; Figueiredo, L. C.; Duarte, P. M.
Abstract : Background and Objective: Comprehension of the similarities and differences in the composition of the subgingival microbiota of patients with diabetes mellitus (DM), smokers or smokers with DM is an important step in developing therapies specific for these groups at risk for periodontitis. Therefore, the aim of this study was to compare the combined and individual effects of DM and smoking on the levels and prevalence of key subgingival periodontal pathogens in patients with chronic periodontitis. Material and Methods: One hundred patients with generalized chronic periodontitis were allocated into one of the following groups: DM (n = 25, non‐smokers with type 2 DM); S (n = 25, non‐diabetic smokers); SDM (n = 25, smokers with type 2 DM); and control (n = 25, non‐diabetic non‐smokers). Two subgingival biofilm samples from healthy sites (probing depth and clinical attachment level ≤3 mm and no bleeding) and 2 from diseased sites (probing depth and clinical attachment level ≥5 mm and bleeding on probing) were analyzed by quantitative polymerase chain reaction for Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola, Eubacterium nodatum, Parvimonas micra, Fusobacterium nucleatum ssp. and Prevotella intermedia . Results: There were no differences among groups in the mean counts of the bacterial species studied, considering all sampled sites (healthy plus diseased sites). There were also no differences among groups regarding the prevalence of any bacteria species in healthy and diseased sites ( P  > .05). The mean P. micra count was significantly higher in the healthy sites of both smoking groups, than in those of the control group ( P  < .05). Conclusion: The subgingival levels and prevalence of the bacterial species studied are not significantly different in subjects with chronic periodontitis presenting DM, smokers or smokers with DM. In addition, DM and smoking, jointly and individually, do not considerably affect the subgingival levels of target periodontal pathogens in patients with chronic periodontitis.